CHICKEN MANURE APPLICATION AND LIMING ENHANCED THE SOIL CHEMICAL PROPERTIES OF ANDISOLS - Alesna, Rene Jane G; Lina, Suzette B (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2024)
The availability of P (Phosphorus) is a major problem in Andisols due to its high P-fixing capacity. Improving the very low P availability is among the challenges in managing Andisols. This study was conducted to determine the timing of lime application in acidic Andisols and to assess the influence of chicken manure application on the availability of P. The experiment was laid out in a split-plot randomized complete block design (RCBD) with eight (8) treatments: main plot (L0 – with lime and L1 – without lime); subplot (T0 – control; T1 - 200-150-100 kg ha -1 N, P 2 O 5 , K 2 O, T2– 5 t ha -1 chicken manure, T3 – 7.5 t ha -1 chicken manure, T4 – 12 t ha-1 chicken manure, T5 – 100-75-50 kg ha -1 N, P 2 O 5 , K 2 O + 5 t ha -1 chicken manure, T6 – 100-75-50 kg ha -1 N, P 2 O 5 , K 2 O + 7.5 t ha -1 chicken manure, and T7 – 100-75-50 kg ha -1 N, P 2 O 5 , K 2 O + 12 t ha -1 chicken manure). Results showed that the sole application of chicken manure or combined with inorganic fertilizers significantly improved the total N, and available P, and lowered the amount of exchangeable Aluminum (Al) and acidity of the soil compared to control. The highest increase in soil available P was observed in T4 (12 t ha-1 chicken manure). Moreover, liming and chicken manure application significantly improved soil pH and decreased exchangeable Al and acidity of Andisols, which facilitates the availability of nutrients.